High-dose corticosteroid associated with catheter-related thrombosis after allogeneic hematopoietic stem cell transplantation. Issue 144 (August 2016) - Zhang, Xiao-Hui; Feng, Fei-Er; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Wang, Yu; Chen, Yao; Fu, Hai-Xia; Mo, Xiao-Dong; Zhang, Yuan-Yuan; Yan, Chen-Hua; Chen, Huan; et al.
Abstract: Background: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients are at an increased risk of thrombotic complications, most of which are catheter-related and present a substantial challenge. The incidence of CRT varies considerably depending on clinical factors. However, the underlying pathogenesis and risk factors remain unclear. Methods: We performed a retrospective nested case-control study in patients following allo-HSCT. Thrombotic episodes were diagnosed based on the clinical suspicion of the physician (pain, swelling, etc.) with subsequent CVC or PICC thrombosis confirmed via duplex ultrasound. Cases with CRT and controls were matched for time of HSCT, age at HSCT, donor source and type of insertion (CVCs or PICC). Results: During the 8-year period, catheters were placed in 2896 patients, with a total of 40 patients (1.38%) developed CRT, among which 11 were associated with CVCs and 29 were associated with PICCs. The median duration from catheter insertion to thrombosis was 97 days. Despite reports of an association between thrombosis and infection, central line-associated bloodstream infection was comparable between groups. No significant differences were noted in terms of primary disease, donor type, conditioning regimen or catheter type between the cases and controls. A multivariate regression analysis identified high-dose corticosteroids as independent risk factors for the development of CRT. CRT seems to negatively affect prognosis in allo-HSCT patients. Conclusion: In conclusion, we demonstrate that the use of high-dose corticosteroids is correlated with the onset of CRT. However, the efficacy and safety of thromboprophylaxis in this population require further investigation. Highlights: Exposure to high dose of corticosteroid is associated with catheter related thrombosis in allo-HSCT patients. Catheter related thrombosis negatively affects prognosis in allo-HSCT patients. The efficacy and safety of thromboprophylaxis require further investigation.